Effect of processing of soybeans on release of free fatty acids and subsequent effects upon fiber digestibilities - Reddy, P. V.; Morrill, J. L.; Nagaraja, Tiruvoor G. (Kansas Agricultural Experiment Station, 2011)
Two in vitro experiments were conducted to determine the rates of lipolysis and biohydrogenation of fat from raw or processed soybeans and to examine subsequent effects upon fiber digestibilities. In experiment 1, substrates containing soy oil; raw soybeans; extruded soybeans; and soybeans roasted at 270,295, or 325 °F were incubated with ruminal contents for 2, 4, 6, 12, or 24 hr, and release of free fatty acids was measured. The fatty acids released from substrates containing soy oil, extruded soybeans, and raw or roasted soybeans reached maximums at 4, 6, and 12 hr incubations, respectively. Fatty acids in roasted soybeans were subjected to less biohydrogenation than those in raw or extruded soybeans, suggesting that fatty acids of roasted soybeans are protected partially from ruminal bacteria. At all incubation times, the substrates containing soy oil or extruded soybeans had lower and those containing roasted soybeans had higher fiber digestibilities.
Keywords: Dairy; Soybeans; Free fatty acids; Biohydrogenation; Fiber digestibilities